Theory On Land Reform: An Overview - Abu Zarin, Hasmah; Bujang, Ahmad Ariffian (Fakulti Ukur dan Harta Tanah, 1994)
In its traditional and generally accepted sense, land reform always meant the redistribution of property rights in land for the benefit of the landless peasants, small farmers and tenants. Land reform has been introduced with the existence of the neo-classical theory. With the advancement of technology in the agricultural and industrial arena, land reform can be related to the economic development which is frequently identified with economic growth that is the average annual rate of increase in real output per capita. This paper attempts to overview the neo-classical theory of land reform in an affort to find out if such theory is still applicable in the present development.